FORMATION OF MANAGERIAL COMPETENCE OF FUTURE POLICE OFFICERS IN THE PROCESS OF PROFESSIONAL TRAINING (Physical Culture and Sport: Scientific Perspective, 2022)
The article substantiates the relevance of the problem of formation and development of managerial competence of future police officers, which is part of the security and defense sector of Ukraine. The definitions of the concepts of "management" and "management competence" are given. Management is a type of human activity, which consists in conscious and purposeful influence on people, objects and processes in order to provide them with the desired parameters of functioning and development.Managerial competence is an integrative quality of an individual who is endowed with management functions, combines essential tools for effective management activities, represented by motivational-value, worldview, communicative components (knowledge, abilities, skills and abilities, etc.), expressed in terms of observed behavior.It is shown that managerial competence has its own complex structure. Specific functions performed by a person performing managerial activities are defined. To the list of specific functions, researchers include motivational-target, organizational-executive, informational-analytical, planning-prognostic, regulatory-corrective functions.Therefore, the process of formation of managerial competence is directly related to the acquisition of managerial abilities and skills that ensure the competent performance of managerial functions. Managerial competence includes not only knowledge, but also cognitive, operational-technological, motivational, ethical, social and behavioral components and a system of value orientations. The formation of managerial competence as a professionally significant personality quality of the future police officer requires the formation of certain knowledge, abilities and skills, as well as certain personality qualities and value orientations, which are components of managerial competence.The formation of abilities, skills, and value orientations is facilitated by the cadets' performance of special exercises and tasks, which in terms of content and conditions are close to real life situations. One of the promising and effective methods of forming abilities, skills and value orientations are trainings and classes with training elements. The results of an experimental study of the formation of managerial competence among future police officers in the process of their professional training are presented. A statistically probable presence of positive dynamics in most indicators in the experimental groups after studying a special course, writing coursework and creative works, and participating in training was revealed.
Keywords: managerial competence; specific managerial functions; components of managerial competence; cadets; officers of the security and defense sector; professional training